Stability of Shrimp Processing Waters during Refrigerated Storage as a Basic for the Isolation of High Value Compounds - Fredeus, Gustaf (My University, 2016)
Huge amounts of water, containing high concentrations of high value compounds today leave the food chain during industrial processing. To stop this waste of high value compounds the water should be cleaned and the molecules recycled back to the food chain. To be able to succeed with this, it is of high importance to know; which high value compounds the waters contain, how to separate the compounds out from the waters and how long these waters can be stored before biochemical changes occurs. In this project, the storage stability of water from a boiling and peeling process of shrimps was investigated. Two types of shrimp process water, from the local company Räkor & Laxgrossisten AB, were stored in a cold room, for 19 days, at a temperature of 4°C. The two process waters examined were steam water taken from the shrimp boiling machine, and so called “main water”, which is a mixture of steam water and peeling water taken at the end of the process line. Two separate storage trials were carried out of each process waters. In order to monitor the quality and stability of the waters during cold storage (4°C) several parameters were examined in the waters; pH, total protein content, ionic strength and color, but also break down components from e.g. lipids and proteins, like primary and secondary products formed during lipid oxidation as well as total volatile nitrogen and odor. Large differences were found between the steam water and the main water in terms of protein concentration and stability over time. The average initial protein concentration for the steam water was found to be 15mg/ml. Its pH was stable around 9 with a small decrease during the last days of storage. The peroxide value (PV) increased from day 0-8 and then decreased from day 9-18. The malondialdehyde (MDA) concentration was stable during the whole storage period; in average 0.7μmol/L. For the olfactory sensory evaluation no significant change could be found during the first 10 day of storage, which was the same for the TVB-N test, but for the two last taken samples (at 13 and 18 days) clear changes in smell and TVB-N value were found. Color and ionic strength did not change significantly over time. The initial pH of the main water was in average 8.58, but at day 18 the pH decreased to 7.20. The protein concentration for the main water was stable for the first 10 days, with an average protein concentration around 1.5mg/ml. The PV increased from day 0-4 and then decreased from day 4-18. The MDA concentrations increased between 4 and 13 days of storage, but were still low even after 18 days of storage, around 2.5μmol/L. Between day 5 to 18 the TVB-N value increased almost linearly and strong odor changes took place between day 4-8, according to the sensory test. Color did not change significantly, while ionic strength, like TVB-N, changed almost linearly from day 4-18. V Overall, the steam water was remarkably stable for all parameters tested during the first 10 days of cold storage, and some parameters like MDA and total protein content, were even stable beyond 18 days of cold storage. The main water was less stable with respect to all parameters tested, probably due to higher microbial growth and less astaxanthin.
Keywords: Livsvetenskaper; Biologiska vetenskaper; Livsmedelsteknik; Livsmedelsvetenskap; Fisk- och akvakulturforskning; Life Science; Biological Sciences; Food Engineering; Food Science; Fish and Aquacultural Science